2017
DOI: 10.3892/or.2017.6069
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/CCR2 axis induces hepatocellular carcinoma invasion and epithelial-mesenchymal transition in�vitro through activation of the Hedgehog pathway

Abstract: Chemokine (C-C motif) ligand 2 (CCL2) has been shown to play an important role in the regulation of tumor cell growth, metastasis and host immune response. CCL2 preferentially binds to the C-C chemokine receptor type 2 (CCR2), which is expressed in various tissues. However, the role of the CCL2/CCR2 axis in hepatocellular carcinoma (HCC) invasion and its molecular mechanisms remain unclear. The aim of this study was to elucidate this issue. The human HCC cell line MHCC-97H was treated with CCL2. Cyclopamine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 41 publications
1
49
1
Order By: Relevance
“…All these results suggested that PLEK2 regulated CCL2 expression through EGFR/STAT3 signaling. Previous studies indicated CCL2 induced EMT process mainly through the activation of transcription factor Snail [44, 45], but in our study, excretive CCL2 protein could partially rescue the inhibitory effects of PLEK2 knockdown by increasing Twist1 and ZEB1 expressions.…”
Section: Discussioncontrasting
confidence: 68%
“…All these results suggested that PLEK2 regulated CCL2 expression through EGFR/STAT3 signaling. Previous studies indicated CCL2 induced EMT process mainly through the activation of transcription factor Snail [44, 45], but in our study, excretive CCL2 protein could partially rescue the inhibitory effects of PLEK2 knockdown by increasing Twist1 and ZEB1 expressions.…”
Section: Discussioncontrasting
confidence: 68%
“…We further evaluated whether PERK activation could contribute to EndMT, which CCL2 has been reported to promote. 33 As shown in Figure 5B, GSK reduced SNAI1 expression, suggesting that UPR activation promoted sarcomagenesis by increasing the release of CCL2 and promoting 34 that both activates 35 and is activated by MTOR. 36 We show for the first time that MTOR activation correlated with bulk macroautophagy and mitophagy dysregulation and that such effects play an important role in KSHV-driven sarcomagenesis.…”
Section: Perk Activation Promotes the Release Of Ccl2 And Contributmentioning
confidence: 83%
“…As expected, we found that the functions of these genes are primarily related to the chemokine signaling pathway, cytokine-cytokine receptor interactions, and the ILK signaling pathway. Previous studies have demonstrated that chemokine signaling pathways play key roles in the proliferation, senescence, angiogenesis, epithelialmesenchymal transition, immune evasion, and metastasis of various cancers (36)(37)(38)(39)(40). ILK, an ankyrin, repeat-containing serine/threonine protein kinase, plays a significant role in biological processes associated with tumorigenesis, including cancer cell proliferation, angiogenesis, metastasis, and drug resistance (41).…”
Section: Discussionmentioning
confidence: 99%